Bio-Inspired Silver Nanoparticles Impose Metabolic and Epigenetic Toxicity to Saccharomyces cerevisiae - Babele, Piyoosh Kumar; Singh, Ashwani Kumar; Srivastava, Amit (Frontiers in Pharmacology, 2019)
AgNPs have many applications in various fields including biomedical applications. Due to a broad range of applications, they considered as a leading fraction of manufactured nanoparticles. AgNPs are synthesized by different types of chemical and biological (green) methods. Previously, biologically synthesized AgNPs were considered safe to the environment and humans. However, new toxicity evidence has initiated a more careful assessment to delineate the toxicity mechanisms associated with these nanoparticles. This study also demonstrates the use of aqueous gooseberry extract for AgNPs preparation in time and cost effective way. UV-Visible spectroscopy, X-Ray Diffraction (XRD), Transmission Electron Microscopy (TEM), and Dynamic Light Scattering (DLS) methods confirm the formation of AgNPs, with an average size between 50-100 nm. Untargeted 1H-NMR based metabolomics revealed many folds up- and down-regulation in the concentration of 55 different classes of annotated metabolites in AgNPs exposed yeast S. cerevisiae cells. On the basis of their chemical nature and cellular functions these metabolites are classified as amino acids, glycolysis and the TCA cycle, organic acids, nucleotide metabolism, urea cycle and lipid metabolism. Transcriptome analysis revealed that the genes involved in oxidative stress mitigation maintain their expression levels while the genes of the TCA cycle and lipid metabolism shows drastic down-regulations upon AgNPs exposure. Moreover, they can induce alteration in the histone epigenetic marks by altering the methylation and acetylation of selected histone H3 and H4 proteins. Altogether, we concluded that selected dose of biologically synthesized AgNPs impose toxicity by modulating the trancriptome, epigenome and metabolome of eukaryotic cells which leads to the disequilibrium in cellular metabolism leading to toxicity.